Challenges of hidden data in the unused area two within executable files - Naji, Ahmed Wathik; Zaidan, A.A.; Zaidan, B.B. (Science Publications, 2009)
Problem statement: The executable files are one of the most important files in operating systems and in most systems designed by developers (programmers/software engineers), and then hiding information in these file is the basic goal for this study, because most users of any system cannot alter or modify the content of these files. There are many challenges of hidden data in the unused area two within executable files, which is dependencies of the size of the cover file with the size of hidden information, differences of the size of file before and after the hiding process, availability of the cover file after the hiding process to perform normally and detection by antivirus software as a result of changes made to the file. Approach: The system designed to accommodate the release mechanism that consists of two functions; first is the hiding of the information in the unused area 2 of PE-file (exe.file), through the execution of four process (specify the cover file, specify the information file, encryption of the information, and hiding the information) and the second function is the extraction of the hiding information through three process (specify the steno file, extract the information, and decryption of the information). Results: The programs were coded in Java computer language and implemented on Pentium PC. The designed algorithms were intended to help in proposed system aim to hide and retract information (data file) with in unused area 2 of any execution file(exe.file). Conclusion: Features of the short-term responses were simulated that the size of the hidden data does depend on the size of the unused area2 within cover file which is equal 20% from the size of exe.file before hiding process, most antivirus systems do not allow direct write in executable file, so the approach of the proposed system is to prevent the hidden information to observation of these systems and the exe.file still function as usual after the hiding process.